Biosynthesis of glycomonoterpenes to attenuate quorum sensing associated virulence in bacteria - Patil, Amrita; Joshi-Navre, Kasturi; Mukherji, Ruchira; Prabhune, Asmita (Biotechnology and Applied Biochemistry, 2017)
The acquisition of multidrug resistance in bacteria has become a bigger threat of late, mainly due to the bacterial signaling phenomenon, quorum sensing (QS). QS, among a population of bacteria, initiates the formation of biofilms and offers myriad advantages to bacteria. Burgeoning antibiotic resistance in biofilm-producing bacteria has motivated efforts toward finding new alternatives to these traditional antimicrobials. In the present study, we report the increased solubility and additional quorum quenching as well as biofilm disruption activity of glyco-derivatives of monoterpenes (citral and citronellal). Glycomonoterpenes of citral and citronellal were synthesized via conjugation of the monoterpenes with glucose by the non-pathogenic yeast Candida bombicola (ATCC 22214). Structural elucidation of newly synthesized glycomonoterpenes showed that one synthesized using citronellal contains three major lactonic forms with molecular weight 492.43, 473.47, and 330.39 Da whereas the one produced using citral has an acidic form with molecular weight 389.33 and 346.23 Da. The glycomonoterpenes were able to individually inhibit QS, mediated through various medium-chain and long-chain N-acyl homoserine lactones (AHLs). These new compounds are interesting additions to the known range of quorum sensing inhibitors (QSIs) and could be further explored for potential clinical applications.